Analysis of Key Factors Affecting Water Disaster in Deep Mining and Establishment of a Water Disaster Evaluation Method Suitable for Different Mining Depths. (6th July 2021) - He, Jianghui; Li, Wenping; Qiao, Wei; Yang, Zhi; Wang, Qiqing
Abstract : Deep mining is the current and future mining focus in the coalfield of North China. Therefore, it is necessary to establish a water inrush assessment method suitable for deep mining. The conventional water inrush coefficient (T ) method is simple to use, but its accuracy is low when the mining depth is very small or large because it neglects the role of the aquifer water yield. The main purpose of this paper is to introduce a simple water inrush risk assessment method that is more applicable in deep mining than the T method. In this study, the hydrogeological characteristics in deep mining were studied and the role of the aquifer water yield in water inrush was analyzed. Afterwards, an improved T method considering the aquifer specific yield (q ) was established. In the new method, the critical water inrush coefficient changes with changing q following a negative correlation. The parameter thresholds were determined based on systematic data analyses of 186 mining cases. The results of the statistical analysis show that the accuracy of the new method at different mining depths is higher than that of the T method.